Application Of Interactive Demonstration Learning Model To Improve Students Learning Outcomes Of Class X MA Hurrasul Aqidah Tarakan In Biology Cross-Interest Learning - Tyas, Oktavianing; Vlorensius, Vlorensius; Ilma, Silfia (Biopedagogia, 2024)
Implementing the right learning model can increase the effectiveness of learning. This research aims to 1) Improve student learning outcomes by implementing the Interactive Demonstration learning model in class The type of research carried out was Classroom Action Research (PTK) with a qualitative approach. The data collection instruments used were end-of-cycle tests, questionnaires, learning model implementation sheets, and documentation. Data analysis was carried out using descriptive statistics. The subjects in this research were 13 students. From the results of the data analysis carried out, the research results showed that student completion in cycle I reached 38.46%. The reason for this is because there are still some students who are less active during the learning process, so improvements need to be made in cycle II. Student learning outcomes in cycle II increased until they reached 100% completeness. Students responded very well to the application of the Interactive Demonstration learning model.